A Note on Quasilinear Elliptic Systems with L∞-Data - Balaadich, Farah; Azroul, Elhoussine (Eurasian Mathematical Journal, 2023)
Abstract. We prove the existence of a weak energy solution for the boundary value problem -div a(x, u, Du) = f in Ω, u = 0 on Ω, where \(Ω\) is a smooth bounded open domain in \(R^n\) (\(n ≥ 3\)) and \(f L^∞(Ω; R^m)\). The existence result is proved using the concept of Young measures.